Lithuanian workers' efforts toward getting an education during the kaiser occupation's oppression in 1915-1917 - Endzinas, A. (Psichologija, 1962)
In the summer of 1914 the First World War began. Due to the threat of invasion of the German army civilians and governorate institutions began evacuation. Also evacuated were the general and special education schools, folk high schools, and almost all of the lower school teachers and Folk High Schools Administrations. A military-occupation management (Ober Ost) was created by area occupied by the German forces connected to East Prussia. It was divided into sections headed by the military government. The Lithuanian working people—who before the 1905 revolution fought against Imperial Russification policies carried out in schools and after 1905 against the czarist regime's reactionary policy manifested itself in school affairs—also had something to say about the German occupation. The invaders carried out policies directed against education. However, the occupants were busy robbing the country and initially limited themselves to the prohibition of Russian language teaching. Local working people benefiting from the 1905 revolution and the evacuation of czarist schools organized schools where the local language was taught. This was done without reactionary bourgeois leadership. The schools were organized lacking qualified teachers. Thus more than a thousand schools were created at the beginning of the occupation. Ober Ost banned organization of schools and issued "ground rules." They expressed anti-education policy, the pursuit of Germanization, and a "kulturtreger" policy of obedience in schools. Implementation of this policy significantly reduced the number of schools. It also consequently decreased the number of students; residents did not want their children going to German schools. The students of these schools were forced to work for the invaders. Behavior with students and teaching staff was atrocious. This was especially manifested in Šiauliai secondary school where the students were beaten. During this period, underground or semi-secret schools became very common. Locals’ activities in the field of education also intensified after the Great October Socialist Revolution. Workers organized a network of secondary schools and special and higher education; these activities intensified even more after the return of refugees. In particular, much was done in the development of Soviet power in Lithuania in 1918.
Keywords: history of pedagogy and history of education; keiser occupation